2013
DOI: 10.1021/co4001315
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of 5-Noranagrelide Derivatives

Abstract: Solid-phase synthesis of 1H-benzo[d]imidazo[1,2-a]imidazol-2(3H)-one derivatives employing Fmoc-α-amino acids and nitroaryl fluorides as key building blocks has been developed. The Fmoc-α-amino acids immobilized on Wang resin, equipped with a piperazine carbamate linker, were transformed to o-nitroanilines in two steps. After reduction of the nitro group, the corresponding o-phenylenediamines gave the 2-aminobenzimidazole scaffold by reaction either with cyanogen bromide or with Fmoc-NCS. Cleavage from the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…In our recent article, it was demonstrated that the configuration remains untouched if the amino acid is immobilized with use of HOBt/DIC strategy . In contrast, full or partial racemization of the α-amino acid stereocenter can occur during the acylation that yields the heterocyclic moiety. To evaluate the stereochemical outcome of the synthetic method, compound 6 DL ( 1 , 1 , 1 ) was prepared as the racemic standard.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent article, it was demonstrated that the configuration remains untouched if the amino acid is immobilized with use of HOBt/DIC strategy . In contrast, full or partial racemization of the α-amino acid stereocenter can occur during the acylation that yields the heterocyclic moiety. To evaluate the stereochemical outcome of the synthetic method, compound 6 DL ( 1 , 1 , 1 ) was prepared as the racemic standard.…”
Section: Resultsmentioning
confidence: 99%
“…Ion pairing between N + (C 4 H 9 ) 4 and S 2 O 4 2− makes the reducing agent soluble in organic media allowing it to diffuse to the nitro compounds. While it has been successfully used for solid-phase synthetic protocols [170,171], our tests reveal that this PTC approach does not produce 15 from 14 in acceptable yields.…”
Section: Selective Reduction Of Nitro Groups In Aa Conjugatesmentioning
confidence: 86%
“…After compound 19 was immobilized on the resin, the reduction of the nitro group was performed using sodium dithionate. It should be noted that the solid-phase reduction with Na 2 S 2 O 4 is typically performed in a biphasic system of DCM/H 2 O with a phase transfer catalyst; in this particular case, the use of Argogel resin enabled the use of aqueous dioxane. Finally, the purine scaffold was cyclized via the corresponding thioureas 23 to obtain the 8-alkyl/arylamino substituted purines 25 .…”
Section: Immobilization Via the C2 Positionmentioning
confidence: 99%